A Case Study in the Development of Fibrinolytic Therapy in a Community Hospital in Indonesia - Handrian Purawijaya; Isabella Anjelin (Malahayati Nursing Journal, 2023)
ABSTRACT Coronary heart disease (CHD) is one of the leading causes of mortality in Indonesia aside from stroke. To reduce the mortality rate, a highly time-dependent, adequate therapy is needed for patients with electrocardiographic features of ST-Elevation Myocardial Infarction (STEMI). The gold standard for reperfusion therapy is thirty minutes for fibrinolytics and ninety minutes for primary PCI. For a community hospital, conducting the reperfusion therapy can be a challenge due to various factors, including human resources, standard operating procedures, and the infrastructure needed. However, to refer the patient to a tertiary hospital often requires time longer than ninety minutes. Therefore, community hospitals should be able to act as the front line of the healthcare system by facilitating fibrinolytic therapy to reduce the mortality rate of CHD in Indonesia. Development of fibrinolytics treatment in community hospitals can be done by creating an expert-reviewed SOP, providing competent human resources, and equipping the hospital with the necessary infrastructure for the service. These are all done in order to keep up with the "golden period" of STEMI patients with a thirty-minute door-to-needle timeframe and reduce the mortality rate caused by ACS in Indonesia. Keywords: Community Hospital, CHD, STEMI, Fibrinolytics.  ABSTRAK Penyakit jantung koroner (PJK) merupakan salah satu penyebab utama kematian di Indonesia selain stroke. Untuk mengurangi angka kematian, terapi yang sangat tergantung waktu dan memadai diperlukan untuk pasien dengan fitur elektrokardiografi ST-Elevation Myocardial Infarction (STEMI). Standar emas untuk terapi reperfusi adalah tiga puluh menit untuk fibrinolitik dan sembilan puluh menit untuk PCI primer. Untuk rumah sakit komunitas, melakukan terapi reperfusi dapat menjadi tantangan karena berbagai faktor, termasuk sumber daya manusia, prosedur operasi standar, dan infrastruktur yang dibutuhkan. Namun, untuk merujuk pasien ke rumah sakit tersier seringkali membutuhkan waktu lebih dari sembilan puluh menit. Oleh karena itu, rumah sakit komunitas harus mampu berperan sebagai garda terdepan dalam sistem pelayanan kesehatan dengan memfasilitasi terapi fibrinolitik untuk menurunkan angka kematian PJK di Indonesia. Pengembangan pengobatan fibrinolitik di rumah sakit komunitas dapat dilakukan dengan membuat SOP yang ditinjau oleh ahli, menyediakan sumber daya manusia yang kompeten, dan melengkapi rumah sakit dengan infrastruktur yang diperlukan untuk pelayanan. Ini semua dilakukan untuk mengimbangi “masa emas” pasien STEMI dengan timeframe door-to-needle tiga puluh menit dan menekan angka kematian akibat SKA di Indonesia. Kata Kunci: RS Komunitas, PJK, STEMI, Fibrinolitik.